A digital puzzle game for the elderly - Barros, P. (2019)
Several works in the literature show the importance that serious digital games have in maintaining the cognitive levels in the elderly population. However, there are important factors which limit their effective use, such as the game rules complexity and diversity, motivation and empathy with the tasks to be carried, users’ abilities to deal with technology (e.g. understanding the functionalities of a mouse device), physical limitations (e.g. mobility, reduced vision), psychological and mental limitations (e.g. reduced memory, social embarrassment), and behaviour limitations as neophobia (i.e. fear of newness or novelty). While addressing the previous factors, serious games need to find an adequate balance between the difficulty required in the game tasks and the user capabilities, in order to be able to maintain the elderly interest but still challenge their cognitive skills. Such implies that serious games for elderly people must have a clear and smooth way to tune the difficulty of the game level. Puzzle games seem to be good candidates for accomplishing the above requirements by changing the number of puzzle pieces, the number of allowed transformations (e.g. rotations, reflexions), colour stimulation, and/or theme selection of the puzzle images. Moreover, the rules are simple and intuitive, and there is a high probability that elderly people have already played some version of a puzzle. In this work, we describe the conception and difficulties behind the implementation of a digital puzzle game targeting the senior population, either institutionalized, being taken care at home, or living autonomously. It is well known that puzzle solving is a highly intensive mental process which strengthens mental fitness and slows the natural degradation process that comes with aging. In our proposed game, we tried not only to create an engaging experience but also, supported by scientific evidence, implement some features to train their mental abilities which are known to degrade over time; in an attempt to slow or even revert such degradation process. Also, since the game data is gathered with the informed consent of all the players, our second aim is to analyse the statistical data collected together with complementary medical information, in order to measure/determine some of the effects of playing digital puzzle games in the long term of mental degradation/fitness. The game is presented with a careful set of images from several sources. A preloaded gallery covers a wide range of popular themes (e.g. animals, nature, social gatherings) and targeting personal issues as the degree of visual impairment and cognitive/memory degradation. To promote further engagement, users can also customize the game experience by selecting themselves images from online resources (as google images) or images stored on their devices. Additionally, relatives or friends may remotely send images to the user’s account which may further promote their willing to play, if the images have some emotional connection attached. By saving data to a central server, caretakers can monitor the elderly activity and difficulties which may help to early diagnose their mental degradation. The proposed game was already used in 4 different elderly care centres, by more than 40 selected seniors with different profiles, in order to evaluate and benchmark the fulfilment of the work aims.